Set Up Security and Integration with the DataPower XI50z for zEnterprise - Credle, Rufus; Cada, Libor; Punwani, Karan; Samejima, Noriyuki; Thomas, Pradeep; Troncone, Corrado (IBM Redbooks, 2011)
This IBM® Redbooks® publication discusses the new IBM WebSphere® DataPower® Integration Appliance XI50 for zEnterprise™ that bridges the gap between mainframe and distributed. The DataPower XI50z (a multifunctional appliance) within the zEnterprise BladeCenter® Extension (zBX) is managed with a single point of control, which can help to streamline operations and maintenance. The DataPower XI50z simplifies the translation of your existing formats to XML (hardware acceleration) for easier communication and connectivity. This book will help you install, tailor, and configure the new attributes for implementing a zEnterprise ensemble network. The zEnterprise System introduces internal virtual networks (VLANs) and additional networking attributes that need to be addressed. Also, we describe the planning considerations for the internal virtual networks and external networks. This book is for anyone who wants an understanding of the security on the zEnterprise that focuses on the usage of the XI50z Network Security Services. As you can expect from an IBM Redbooks publication, we provide several integration use cases that you are able to use immediately within a production environment, for example, the XI50z connecting with and using WebSphere MQ (WMQ), connecting with CICS®, connecting with IMS™, and connecting with DB2®.